Perancangan Program Aplikasi Kartu Nama Digital - Muttaqien, Muhammad Fauzan ‘Adli; Dahliyusmanto, Dahliyusmanto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Business card is a card that can deliver some informations related to company or even professionals, but some people in business such as professionals and companies doesn’t have business card or only some of them have business cards for reasons such as the funds spent on making business cards for many employees are too large for the scale of a business as big as a company, and feel that business cards are not very important for professionals. With Augmented Reality Technology, business cards can be converted into digital form so it can be easily accessed by many people and certain people, and relatively low production costs than conventional business cards. The use of Augmented Reality technology by scanning digital business cards as markers in the form of texts and images, and displays an object on a marker. Digital business cards are divided into two types, namely business cards for public use and business cards for use in business which will appear if successfully scanned using a marker. Create and process digital business cards, design and upload markers, design application interfaces, and design Augmented Reality technology in the form of Android Package Kit (APK). Development of this application requires several tools, such Unity 3D, Vuforia SDK, Android SDK, Adobe Photoshop, and Adobe Premier. This study resulted an Android-based application with Augmented Reality Technology as a medium for displaying digital business cards by scanning markers using a smartphone, so users can see digital business cards have better informations.Keywords: Augmented Reality, Marker, business cards, kartu nama digital.